2015
DOI: 10.1080/10408398.2012.717976
|View full text |Cite
|
Sign up to set email alerts
|

The Glycemic Index of Rice and Rice Products: A Review, and Table of GI Values

Abstract: Rice is the principle staple and energy source for nearly half the world's population and therefore has significant nutrition and health implications. Rice is generally considered a high glycemic index (GI) food, however, this depends on varietal, compositional, processing, and accompaniment factors. Being a major contributor to the glycemic load in rice eating populations, there is increasing concern that the rising prevalence of insulin resistance is as a result of the consumption of large amounts of rice. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
1
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(135 citation statements)
references
References 259 publications
6
116
1
12
Order By: Relevance
“…roller, hammer, disc and stone) to reduce particle sizes for subsequent processes or uses (Doblado-Maldonado et al, 2012;Li et al, 2014a). Milling affects starch digestibility, and various studies generally reported an inverse relationship (Table 2) between starch digestibility and particle size (Li et al, 2014a;Tosh & Chu, 2015;Kaur et al, 2016). Milling affects starch digestibility, and various studies generally reported an inverse relationship (Table 2) between starch digestibility and particle size (Li et al, 2014a;Tosh & Chu, 2015;Kaur et al, 2016).…”
Section: Milling or Grindingmentioning
confidence: 99%
See 3 more Smart Citations
“…roller, hammer, disc and stone) to reduce particle sizes for subsequent processes or uses (Doblado-Maldonado et al, 2012;Li et al, 2014a). Milling affects starch digestibility, and various studies generally reported an inverse relationship (Table 2) between starch digestibility and particle size (Li et al, 2014a;Tosh & Chu, 2015;Kaur et al, 2016). Milling affects starch digestibility, and various studies generally reported an inverse relationship (Table 2) between starch digestibility and particle size (Li et al, 2014a;Tosh & Chu, 2015;Kaur et al, 2016).…”
Section: Milling or Grindingmentioning
confidence: 99%
“…The prominent ones are rice and maize, as well as porridges or gruels that could have undergone minimal heat-moisture treatments (e.g. Stapley et al (1997) measured increases in starch gelatinisation with boiling time for wheat grains, and Kaur et al (2016) reported increases in glycaemic responses of rice with boiling time and water:grain ratios. Cooking temperatures vary depending on products, so also are time and water:grain ratios .…”
Section: Boilingmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing the results for the glucose and insulin curves, we may observe that the GI values fall within the lower values observed among all the types of rice (Kaur et al 2016) and even below the threshold of low GI foods, that is 55 (Wolever et al 2006). Rice is generally considered a high GI food, but this depends on varietal, compositional and processing factors.…”
Section: Discussionmentioning
confidence: 99%